Pengaruh Kredit Terhadap Peningkatan Pendapatan Anggota Pada Koperasi Simpan Pinjam Makmur Bersama - Anemala Zai; Dyah Palupiningtyas (Universitas Sains dan Teknologi Komputer, 2024)
This research investigates the impact of credit services provided by Makmur Bersama Savings and Loan Cooperative on the income of its members in three main dimensions, namely credit contribution, credit services, and business improvement through credit services. The research employs a quantitative approach using the SPSS version 22 statistical tool. The study was conducted in the Jati Rungo Village, Pringapus District, Semarang Regency, Central Java, with the entire population of members serving as the sample. The results of the analysis indicate that the credit contribution variable has a relatively small but significant influence on member income, while the credit services and business improvement through credit services variables have a positive and significant impact on member income. Simultaneous hypothesis testing confirms the significant effect of at least one independent variable on member income. In conclusion, the observed factors such as credit contribution, credit services, and business improvement through credit services have a significant influence on cooperative member income, providing crucial insights for cooperative management to enhance services and financially empower their members.